THE ROLE OF AUGMENTED REALITY (AR) TECHNOLOGY IN ENHANCING CONSUMER EXPERIENCE: A MARKETER'S AND CONSUMER'S PERSPECTIVE IN THE RETAIL INDUSTRY - Saeful Zaman, Jajang (Nusantara Journal Of Management Business (NUMABI), 2025)
This study explores the role of Augmented Reality (AR) technology in enhancing consumer experience in the retail industry, focusing on both marketer and consumer perspectives. Using a literature review approach, the study finds that AR significantly improves consumer experience by providing clearer and more interactive product visualizations and facilitating decision-making through product simulations. From a marketer's perspective, AR is used as a strategic tool to create unique shopping experiences and differentiate brands. However, key challenges include development costs, integration with existing systems, and user training. Consumer acceptance of AR also varies based on demographic factors and personal preferences. The findings indicate that while AR offers many benefits, its implementation requires careful consideration of costs and training, as well as adaptation of strategies to meet diverse market needs. Keywords: Augmented Reality (AR), Consumer Experience, Retail, Marketer Perspective, Interactive Visualization, Decision-Making, Implementation Challenges, Technology Adoption